Supporting older adults with mobility disabilities through voice-activated digital assistants and smart home technologies - Jaewon Kang; Emma Lachs; Kathryn Huang; Laura A. Rice; Wendy A. Rogers (Gerontechnology)
Background: Older adults aspire to maintain their autonomy in their preferred environments and remain active in their community. However, disabilities or age-related changes can present obstacles to achieving this goal. Voice-activated digital assistants and smart home technologies are potential solutions to support older adults. However, widespread implementation of these technologies has not been explored for older adults with mobility disabilities, who may have unique needs. Research aim: This study investigated how voice-activated digital assistants and connected smart home technologies can specifically benefit older adults with mobility disabilities, with the provision of facilitating conditions such as instructional support for initial and continued use. Method: We provided twenty-four community-dwelling older adults with mobility disabilities with an Amazon Echo Show, a smart plug, and a smart light, along with instructional manuals tailored to their needs. Participants were taught to install the technologies and asked to use them for five weeks. We assessed their overall technology readiness and pro- ficiency, feelings of loneliness, and ability to use smart home technologies. We conducted in-depth interviews to gain deeper insights into their experiences and perspectives. Results: Step-by-step instructional manuals supported their successful installation and utilization of the provided technologies. Participants reported good usability and high confidence in using these technologies. Qualitative analysis showed that these technologies improved functional independence by enabling participants to control their home environment remotely, increase safety, and enable them to access up-to-date information. They had a significant reduction in loneliness after 5 weeks (p = .003), attributed to increased social connections and entertainment and viewing the voice-activated digital assistants as companions. Conclusion: Voice-activated digital assistants and smart home technologies have the potential to support older adults with mobility disabilities, assuming the right resources are provided to facilitate utilization. Healthcare professionals and researchers should recognize the unique benefits of these technologies for this population to promote their adoption and use effectively.